Application Of the Expository Learning Method In Understanding The Perception Of Hijaiyah Letter Forms In 'Mild Mentally Retarded' Students At SLB YPLB-LB Hegar Asih - Zul Andrivat; Aan Hasanah; Badrudin Badrudin; Dewi Sadiah (International Journal of Science Education and Technology Management, 2026)
This research is motivated by the low abilities of students with special needs, especially those classified as "mild mentally retarded" in recognizing and understanding the shape of the Hijaiyah letters. This difficulty is caused by limitations in visual perception and the lack of learning methods that are appropriate to their characteristics and learning needs. The purpose of this study is to evaluate the effectiveness of these methods in the context of Islamic religious education learning in a special school environment. The approach used in this study is a qualitative approach with a case study method. The study was conducted on a small group of students "mild mentally retarded" at SLB YPLB-LB Hegar Asih Cipaganti Bandung. Data collection was conducted through observation, interviews with teachers, and documentation of learning activities. The results of the study indicate that the application of the methodExpository Learning has a positive impact on the development of students' perception of the shape of the Hijaiyah letters. Students showed significant improvements in recognizing, naming, and writing the Hijaiyah letters with a higher level of accuracy compared to before the implementation of this method. In addition, interactions between teachers and students became more active and communicative, and learning became more structured and easier to understand for students with special needs. The results of the study indicate that the Hijaiyah methodExpository Learningeffective in improving students' visual perception "mild mentally retarded" to the shape of the Hijaiyah letters. Students become more focused, can differentiate letter shapes gradually, and show improvement in recognizing and remembering the Hijaiyah letters. Structured learning, the use of visual media, and systematic explanations help students better understand the material, making the learning process more optimal and meaningful.